2003
DOI: 10.1108/09564230310474174
|View full text |Cite
|
Sign up to set email alerts
|

Customer complaining behaviour in technology‐based service encounters

Abstract: Compares complaining behaviour in traditional and technology-based service encounters. Drawing on 160 negative critical incidents within Finnish retail banking, shows that, contradictory to common predictions, there are no significant differences in the complaining rates between the two types of service encounters. Attributes this finding to the high reliance of traditional complaining methods in both types of service encounters. Finds, however, that complaints about technology-based service encounters have si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 14 publications
2
78
0
1
Order By: Relevance
“…(2003) Technology acceptance model applied to Internet banking. Snellman & Vihtkari (2003) Complaining behaviour in Finnish retail banking. Curran & Meuter (2005) Factors that infl uence attitude and intention to use ATMs, phone, and online banking.…”
Section: Service Blueprinting Relevant Conceptsmentioning
confidence: 99%
“…(2003) Technology acceptance model applied to Internet banking. Snellman & Vihtkari (2003) Complaining behaviour in Finnish retail banking. Curran & Meuter (2005) Factors that infl uence attitude and intention to use ATMs, phone, and online banking.…”
Section: Service Blueprinting Relevant Conceptsmentioning
confidence: 99%
“…As the latter facet involves enterprise scales, facility elements (such as style, material, and design aesthetics), and social factors, the types of service encounters are classified into technology-based and interpersonal-based encounters (Bitner et al, 1994;Bettencourt & Gwinner, 1996;Crosby, Evans, & Cowels, 1990;Dolen & Ruyter, 2002;van Dolen, de Ruyter, & Lemmink, 2004;Parasuraman & Zinkhan, 2002;Snellman & Vihtkari, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Customer complaining behavior in technology-based service encounters was further studied by Snellman and Vihtkari (2003) who found that in the Finnish banking industry, there were no significant differences in the complaining rates of customers who complained via traditional means and those who complained via technologymediated service encounters. The research conducted to date suggests that more work is needed, as the findings of industry specific customer complaining behavior will have interesting implications for designers of service recovery mechanisms.…”
Section: Consumer Complaining Processmentioning
confidence: 99%